The Concept of Yonisomanasikāra ‘Proper Attention’ as a Buddhist Way to Social Peace - Ven. Acchariya , (Journal of International Buddhist Studies, 2022)
The topic of this study is the concept of Yonisomanasikāra ‘Proper Attention’ as a Buddhist way to social peace. There are three objectives, namely: - 1) To study the concept of “Yonisomanasikāra (Proper attention)” in Buddhist canonical texts and other related contexts, 2) To examine the Theravāda Buddhist perspective on the cause of social conflict and way to prevent conflict, and 3) To apply Yonisomanasikāra ‘Proper Attention’ as a Buddhist way to social peace. Research methodology will be methods and theory used in the field of peace studies, specifically religion and peace. The results show that the Concept of Yonisomanasikāra can be described as thinking in terms of causal relationships, such as the consequences of one’s thoughts and actions, or exploration of the conditioned nature of phenomena which will lead to the development of insight or wisdom. Yonisomanasikāra was instrumental in arousing the wisdom that led to realization; and that Greed (Lobha) is also one of the causes of social conflict. Non-Greed (Alobha) is the way to prevent that greed (Lobha). Anger (Dosa) is one of the causes of social conflict. Loving-kindness (Adosa) is the way to prevent that anger (Dosa). Ignorance (Moha) is one of the causes of social conflict. Wisdom (Amoha) is the way to prevent that ignorance (Moha). Social peace is a way of sustaining social life distant from internal conflict. It is one of the objectives of social politics, which offer peaceful solutions to the disputes and conflicts that may arise from disagreements and social tensions among national and international various sectors of society. Peace is a concept of societal friendship and harmony in the absence of hostility and violence. This study is significant because of: 1) Knowing about the concept of Yonisomanasikāra (Proper Attention) in Theravāda Buddhism, 2) Clearly understanding the cause of social conflict and way to prevent conflict, and 3) Realization of the application of Yonisomanasikāra ‘Proper Attention’ as a Buddhist way to social peace.